2023
DOI: 10.3390/lubricants11120534
|View full text |Cite
|
Sign up to set email alerts
|

Dual Network Co-Crosslinked HNBR Composites with Enhanced Tribological Properties under Water Lubrication

Hao Yu,
Wuxuan Zheng,
Caixia Zhang
et al.

Abstract: Water-lubricated bearings play a critical role in underwater propulsion systems but are often prone to failure due to mechanical wear and vibration, especially under high loads and prolonged friction. In response to this issue, our study introduces a novel approach: a dual network co-crosslinking strategy utilizing hydrogenated nitrile butadiene rubber (HNBR). This strategy connects the rubber network with the epoxy network through epoxidized Eucommia ulmoides gum. A comprehensive analysis was conducted to ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, the Si dispersed on the surface has a limited role in the abrasive wear [18]. The structural characteristics of SiC as the bone along with the self-lubricating graphite particles dispersed on the surface [29] ensure that the siliconized graphite maintains a relatively low wear depth of 0.97 µm compared to that of the other bearing materials [10][11][12][13]. The load is insufficient to completely smooth all the rough asperities within a 7200 s duration under 500 N with 100 rpm, which results in some wear ploughs on the surface, and the wear depth decreases to 0.65 µm, suggesting that the siliconized graphite is currently under boundary lubrication but is transitioning towards mixed lubrication with limited lubrication from water, and the loading is mainly sustained in direct contact.…”
Section: Lubrication Regimes In High-temperature and High-pressure Watermentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Si dispersed on the surface has a limited role in the abrasive wear [18]. The structural characteristics of SiC as the bone along with the self-lubricating graphite particles dispersed on the surface [29] ensure that the siliconized graphite maintains a relatively low wear depth of 0.97 µm compared to that of the other bearing materials [10][11][12][13]. The load is insufficient to completely smooth all the rough asperities within a 7200 s duration under 500 N with 100 rpm, which results in some wear ploughs on the surface, and the wear depth decreases to 0.65 µm, suggesting that the siliconized graphite is currently under boundary lubrication but is transitioning towards mixed lubrication with limited lubrication from water, and the loading is mainly sustained in direct contact.…”
Section: Lubrication Regimes In High-temperature and High-pressure Watermentioning
confidence: 99%
“…Siliconized graphite is primarily used for water-lubricated thrust bearings in the highloading systems of a primary coolant loop under a loading pressure of up to 0.8 MPa at a water temperature of 70-90 • C [8,9]. Compared with the thrust bearing materials of polymers [10,11], composites [12,13], and ceramics [14,15], etc., the tribological behaviors of siliconized graphite under water lubrication is more complex, due to its multi-phase structure and microstructure. Xia et al [16] found that the ploughing wear of siliconized graphite is mainly a dry wear mechanism coupled with abrasive and adhesive wear, resulting in a lower wear rate but in a higher coefficient of friction (COF).…”
Section: Introductionmentioning
confidence: 99%
“…SBS, SBR, and PB are mostly used to manufacture of tires. Nitrile-butadiene rubber (NBR), hydrogenated nitrile-butadiene rubber (HNBR), fluoroelastomer (FKM), and Tetrapropyl fluororubber (FEPM) have good mechanical properties, and can be used in room temperature and high temperature environment sealing [4][5][6].…”
Section: Introductionmentioning
confidence: 99%